Spatial filter and its application in three-dimensional single molecule localization microscopy - Fan, X; Hendriks, J; Comini, M; Katranidis, A; Büldt, G; Gensch, T (IOP Publishing, 2020)
Single molecule localization microscopy (SMLM) allows the imaging of cellular structures with resolutions five to ten times below the diffraction limit of optical microscopy. It was originally introduced as a two-dimensional technique based on the localization of single emitters as projection onto the x-y imaging plane. The determination of the axial position of a fluorescent emitter is only possible by additional information. Here we report a method (spatial filter SMLM (SFSMLM)) that allows to determine the axial positions of fluorescent molecules and nanoparticles on the nanometer scale by the usage of two spatial filters, which are placed in two otherwise identical emission detection channels. SFSMLM allows axial localization in a range of ca. 1.5 μm with a localization precision of 15 - 30 nm in axial direction. The technique was utilized for localizing and imaging small cellular structures - e.g. actin filaments, vesicles and mitochondria - in three dimensions.